2009
DOI: 10.1002/elps.200800745
|View full text |Cite
|
Sign up to set email alerts
|

The serum protein binding of pharmacologically active gallium(III) compounds assessed by hyphenated CE‐MS techniques

Abstract: Transition metal-based drugs exhibit high affinity to the soft donors of human serum proteins, especially of the high-abundance protein HSA and of transferrin (Tf), whereas Ga(III) salts are known to bind to Tf and other iron-containing metalloproteins, thereby interfering with the iron metabolism. Herein, the utilization of CE-MS methods for studying the binding behavior of a therapeutic gallium nitrate formulation and the anticancer drug candidate Tris(8-oxyquinolinato)gallium(III) to Tf and HSA under simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 63 publications
1
41
2
3
Order By: Relevance
“…Binding of Ga(III) to the iron site of the R2 subunit of this enzyme results in the destabilization of the tyrosyl radical essential for enzymatic activity [9]. Ga(III) is able to bind to the iron sites of transferrin, which promotes the cellular absorption of Ga(III) [10], in particular in proliferating cancer cells with strong iron demand and overexpressed transferrin receptors, although cellular gallium uptake may also occur by a transferrin-independent pathway [5,9].…”
Section: Tris-ligand Ga(iii) Complexes and Tris(3-hydroxy-2-methyl-4hmentioning
confidence: 99%
“…Binding of Ga(III) to the iron site of the R2 subunit of this enzyme results in the destabilization of the tyrosyl radical essential for enzymatic activity [9]. Ga(III) is able to bind to the iron sites of transferrin, which promotes the cellular absorption of Ga(III) [10], in particular in proliferating cancer cells with strong iron demand and overexpressed transferrin receptors, although cellular gallium uptake may also occur by a transferrin-independent pathway [5,9].…”
Section: Tris-ligand Ga(iii) Complexes and Tris(3-hydroxy-2-methyl-4hmentioning
confidence: 99%
“…Although its affinity is reduced compared to that of Fe 3+ , when in excess, Ga 3+ replace Fe 2+ from this protein [41]. Nevertheless, using gel electrophoresis autoradiography experiments with 67 Ga and 59 Fe, it was shown that the two ions in fact entail slightly different pathways of entry and efflux into cells. Additionally, and perhaps not unexpectedly due to its increased solubility, Ga, unlike Fe 3+ , is not sequestered inside cells by ferritin [42].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…This method efficiently provides valuable information about binding parameters, including changes in the content of gallium-protein adducts and equilibrium binding constants [58]. Other studies used CE-MS to evaluate the binding of gallium nitrate and gallium quinolate to transferrin and human serum albumin [59]. Having similar coordination geometries and strong affinity for groups that contain oxygen, Ga 3+ is used as a substitute for Fe 3+ in some applications regarding iron-binding proteins and binding of phosphopeptides.…”
Section: Derivatives Of (Ethylenediamine)-nn′-bis-[propyl[(2-hydroxymentioning
confidence: 99%
See 1 more Smart Citation
“…Ugyanakkor az ezt jóval meghaladó in vivo mérhető maximális szérumkoncentrációk arra utalnak, hogy a véráramban nagyobb részt fehérjékhez kötődik [67]. CE-MS vizsgálatok szerint a fémion szinte kizárólag Tf-hez kötődött, míg a HSA szerepe igen mérsékelt volt [72]. Másrészről röntgenabszorpciós spektroszkópiás mérések szerint a fémion körüli koordinációs szféra nem változott sem Tf, sem HSA jelenlétében, ami a nem koordinatív, másodlagos kötésmódok lehetőségét veti fel [73].…”
unclassified